DETERMINAN ANALISIS KINERJA BANK BERDASAR METODE AHP ( ANALITICAL HIERARCHY PROCESS - Dipateruna Teruna Awaludin; Asyari Asyari; Deny Hidayatullah; Muhammad Nur (JURNAL REKAYASA INFORMASI, 2024)
Balanced Scorecard is a performance measurement and management system which regards the company from four perspectives, namely financial perspective, customer, internal business process and learning and growth. Bank Mandiri has implemented a Balanced Scorecard performance measurement system with AHP Method. That's why the writer wanted to know how the application of balanced scorecard during this run the company and examine its impact on the company's performance. The method used in this research is descriptive explanatory with analitical hierarcy process. Data collection techniques include primary data by conducting interviews, deployment questioner and direct observation and secondary data to obtain documentation of the company and literature related to the research topic. Results of research have shown that the application of the balanced scorecard as a performance measurement system PT. Bank Mandiri Tbk. has executed quite well. Advantages and disadvantages of performance in each perspective an impact either directly or indirectly to the performance in other perspectives to the financial perspective. Performance of non-financial perspective can be considered good enough only still needed improvement as well as improvement in some aspects of the financial perspective while the performance has decreased, although not significantly. Keywords: Balanced Score card, Financial Performance. Analitical hierarcy process